Occult insulinoma in a Meckel’s diverticulum: a case report - Pandya, Bharati; Narang, Ravinder; Jajoo, Ulhas N. (International Surgery Journal, 2016)
Insulinoma is a deceptive endocrine tumour of the pancreas due to its bizarre and nonspecific symptom complex. It is also difficult to localize preoperatively, especially when present in an ectopic location. A 65 year old woman presented with recurrent episodes of hypoglycaemia. She was erroneously under treatment for psychotic disorder. A suspicion of insulinoma led us to investigate her further. Investigations revealed fasting hypoglycaemia, endogenous hyperinsulinism, and a pancreatic parenchymal lesion. On exploration, an incidental Meckel’s diverticulum with a nodule was also found. Histopathology showed an insulinoma of the Meckel’s diverticulum and a benign non-functioning adenoma in the pancreatic nodule. Surgery eventually resulted in restoration of euglycaemia and complete disappearance of patient’s symptoms.